Impact of Uterine Adenomyosis on Pregnancy Outcomes in Women Undergoing In Vitro Fertilization Treated With a Long-Term Pituitary Downregulation Protocol - Zhang, Jiaxin; Hu, Linli; Bu, Zhiqin; Sun, Yingpu (Frontiers in Endocrinology, 2021)
Background Some studies have demonstrated that adenomyosis patients can achieve a comparable pregnancy outcome with women with normal uteruses, while there is no unanimous conclusion at present. Method We recruited 65 adenomyosis patients and 260 frequency-matched control women with endometriosis at a ratio of 1:4 according to age. Clinical pregnancy rate, spontaneous abortion rate, and live birth rate were compared between these two groups after controlling other factors. Results Compared with endometriosis patients, adenomyosis patients had a higher antral follicle count (AFC) (12.71 vs 11.65, P=0.027). Though the two groups had the same number of embryos transferred, adenomyosis patients had an obviously declined implantation rate (31.91% vs 46.74%, P=0.005), clinical pregnancy rate (47.06% vs 64.42%, P=0.028), live birth rate (31.37% vs 54.81%, P=0.004), and significantly increased spontaneous abortion rate (33.33% vs 13.43%, P=0.034). Multivariate logistic regression analysis showed that adenomyosis had adverse influences on pregnancy outcome when age and the number of embryo transfers were controlled (adjusted OR=0.361, P=0.003). Conclusion Even after being matched with age, adenomyosis still had adverse influences on the pregnancy outcome of IVF in patients undergoing the long protocol.